Building Learning Communities in Residential Colleges - Muldoon, Robyn; Macdonald, Ian (Journal of University Teaching and Learning Practice, 2009)
This paper addresses the retention issues presented when large numbers of students from low socio-economic backgrounds and associated disadvantaged educational histories live together on-campus. It reports research in progress on a new approach taken at the University of New England (UNE), Australia, aimed at encouraging the growth of learning communities in colleges through the training and subsequent support of senior students charged with helping first year students negotiate the transition to successful university study. It outlines the issues faced by both the first year students and the senior students, strategies implemented, outcomes to date and plans for further change. UNE is a regional university with 5,000 on-campus students, half of whom live in seven residential colleges. It appears that for these students, traditional lectures and workshops on learning strategies and techniques are not as effective as layered, personal ‘at the elbow’ learning support in a non-threatening, social environment.